2016
DOI: 10.1002/anie.201604917
|View full text |Cite
|
Sign up to set email alerts
|

A Terminal Osmium(IV) Nitride: Ammonia Formation and Ambiphilic Reactivity

Abstract: Low-valent osmium nitrides are discussed as intermediates in nitrogen fixation schemes. However, rational synthetic routes that lead to isolable examples are currently unknown. Here, the synthesis of the square-planar osmium(IV) nitride [OsN(PNP)] (PNP=N(CH2 CH2 P(tBu)2 )2 ) is reported upon reversible deprotonation of osmium(VI) hydride [Os(N)H(PNP)](+) . The Os(IV) complex shows ambiphilic nitride reactivity with SiMe3 Br and PMe3 , respectively. Importantly, the hydrogenolysis with H2 gives ammonia and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 44 publications
3
51
0
Order By: Relevance
“…For example, a very active heterogeneous Ru catalyst is used in the industrial Kellog Advanced Am-monia Process (KAAP), 5 and the first metal-dinitrogen complex to be discovered featured ruthenium ((NH 3 ) 5 Ru-N 2 2+ ). 6 Noteworthy achievements in Ru and Os model chemistry have included (1) the demonstration of terminal nitride (M=N [2/3+] ) coupling to form (iso- lable or transient) N 2 -bridged bimetallics of the type L n M-N 2 - ML n [4/5/6+] (M = Ru or Os); 7,8 (2) photochemically induced homo- lytic N 2 cleavage to generate terminal Os≡N products; 9 (3) selective protonation and hydrogenation of terminal osmium nitrides to generate NH 3 ; 10 and (4) step-wise NH 3 oxidation to N 2 via diimide (HN=NH) and hydrazine (N 2 H 4 ) intermediates at cofacial Ru porphyrins. 11 …”
mentioning
confidence: 99%
“…For example, a very active heterogeneous Ru catalyst is used in the industrial Kellog Advanced Am-monia Process (KAAP), 5 and the first metal-dinitrogen complex to be discovered featured ruthenium ((NH 3 ) 5 Ru-N 2 2+ ). 6 Noteworthy achievements in Ru and Os model chemistry have included (1) the demonstration of terminal nitride (M=N [2/3+] ) coupling to form (iso- lable or transient) N 2 -bridged bimetallics of the type L n M-N 2 - ML n [4/5/6+] (M = Ru or Os); 7,8 (2) photochemically induced homo- lytic N 2 cleavage to generate terminal Os≡N products; 9 (3) selective protonation and hydrogenation of terminal osmium nitrides to generate NH 3 ; 10 and (4) step-wise NH 3 oxidation to N 2 via diimide (HN=NH) and hydrazine (N 2 H 4 ) intermediates at cofacial Ru porphyrins. 11 …”
mentioning
confidence: 99%
“…It was shown that most of the d‐block metals may be embedded within the binding pockets of the different pincer scaffolds shown in Scheme and Scheme although there are transition metal that remain to be explored in that context (see Scheme ). It is notably that all the metals that have not yet been coordinated to N ‐heterocyclic PNP pincers, were shown to form alkylamide‐, arylamide‐ or silylamide‐based PNP pincer complexes . It therefore seems likely that for these metals N ‐heterocyclic PNP pincers will also prove to be useful ancillary ligands.…”
Section: Future Directionsmentioning
confidence: 99%
“…Indeed, raising the electron count at the metal can facilitate metal‐centered activation of small molecule coupling partners . High electron count ( d ≥4) nitrides are uncommon, and unknown for early metals. They can display enhanced reactivity, including nitride hydrogenolysis and carbonylation .…”
Section: Figurementioning
confidence: 99%
“…High electron count ( d ≥4) nitrides are uncommon, and unknown for early metals. They can display enhanced reactivity, including nitride hydrogenolysis and carbonylation . Though electrophilic functionalization via alkylation, protonation, and silylation, of terminal nitrido groups is well reported, redox‐coupled transformations are uncommon, despite representing an efficient means of using nitrides as N‐atom building blocks .…”
Section: Figurementioning
confidence: 99%